ANALISA PANJANG ANTRIAN PADA LOKET PEMBELIAN KARCIS DI PUSKESMAS SEMANAN KALIDERES - ABDUL HARIS LAHUDDIN; YENNY WIDIANTY (Faktor Exacta, 2012)
Line queue up is to represent phenomenon which often happened when request to an service periodically exceed capacities by then. Puskesmas Semanan represent one of the health service sector which in it give service to certain society during is often given on to less well-balanced situation among/between service time given by officer with arrival storey; level from all patient. This matter is caused by penataletakan of less up to standard job/activity station, So that cause line queue up very long. To overcome this matter, hence used by queue method, is so that expected can lessen expense await and lay time old ones. As for stages; steps which is used in this trouble-shooting that is : antecedent observation as a mean to know existing problem globally, formulation of is problem of, determination of is target of research, research methodologies, survey which good for collecting needed by data that is station work early, time between arrival, service time early, employees salary and earnings from all patient, data sale of ticket 4 the last year and after repair of job/activity station, reassembled by service time data after repair. After data gathered, to be done/conducted by test sufficiency of data, data distribution test, data analysis with queue method, forecasting 5 year come, determination of is amount of optimal station and make conclusion. By doing/conducting repair of job/activity station, hence can improve service time efficiency equal to 28,3 %, namely from 2,5079 minute / patient become 1,7970 minute / patient. Keywords : data analysis with queue method, sufficiency of data, data distribution test.